Mitigating the risk that peer-initiated task conflict escalates into diminished helping: roles of passion for work and collectivistic orientation - De Clercq, D.; Pereira, R. (International Studies of Management and Organization, 2022)
This study unravels the link between employees’ exposure to peer-initiated task conflict—defined as the extent to which they perceive that coworkers systematically contest and attack their opinions—and their engagement in helping behavior. Beliefs about interpersonal conflict might mediate this link, and two personal resources, passion for work and collectivistic orientation, arguably have moderating roles. To test these predictions, this study relies on survey data from employees who work in the banking sector, which confirm that peer-initiated task conflict diminishes helping behavior, because the focal employees come to believe coworkers are responsible for their emotion-based quarrels. Employees’ passion for work and collectivistic orientation buffer this harmful dynamic. Organizations thus should recognize that exposure to overcritical colleagues can undermine voluntary work behaviors, as well as consider how they might help reduce the force of this negative dynamic by enabling employees to find ways to draw from their supportive personal resources.